The frequency of Hashimoto thyroiditis in children and the relationship between urinary iodine level and Hashimoto thyroiditis - CESUR, YAŞAR; Dogan, Murat; Acikgoz, Emel; ACIKGOZ, Mehmet; Cesur, YAŞAR; ARIYUCA, Sevil; BEKTAS, Mehmet Selcuk (My University, 2011)
The aim of this study was to determine the frequency of thyroid autoimmunity in second grade primary school students and to examine the relationship between iodine and Hashimoto thyroiditis (HT). This was a cohort study performed with 1000 students. Urinary iodine levels, antithyroid peroxidase (anti-TPO) and antithyroglobulin (anti-Tg) antibodies were determined in all children. Children with anti-TPO or anti-Tg antibody positivity or with goiter were summoned for detailed examinations. In total, 36 cases (3.6%) were diagnosed as HT. The goiter frequency was found in 17.5% of the whole cohort. Additionally, iodine deficiency was found in 64.2% of all children. The median urinary iodine excretion was determined as 132 mu g/L (range 382 mu g/L) in the HT group, whereas it was 73 mu g/L (range 390 mu g/L) in children with goiter but without HT and 81 mu g/L (range 394 mu g/L) in normal children. The urinary iodine level of HT cases was significantly higher than the other two groups (p < 0.001). HT was also determined in 2% of patients with low urinary iodine levels, in 6.2% of patients with normal urinary iodine levels, and in 7.5% of patients with high urinary iodine levels. Our data demonstrates the close relationship between excessive iodine levels and autoimmunity.